Musculoskeletal Disorders among Brazilian Dentists in São Paulo - Soares, Gabriella Barreto [UNESP]; Siqueira, Carlos Eduardo; Estrada-Martínez, Lorena; Garbin, Cléa Adas Saliba [UNESP]; Garbin, Artênio José Ísper [UNESP] (EDIPUCRS, 2019)
Objective: This study aimed at investigating the relationships between health and work-related musculoskeletal disorders (WMSDs) in dentists, and the relationship with socio-demographic, work and health variables. Methods: We conducted a cross-sectional study of 204 dentists who work in public clinics in the state of São Paulo, Brazil. We used a self-administered survey that included questions on sociodemographic and health aspects, work-related factors, and the Nordic questionnaire. Results: WMSDs were often reported in the neck, shoulder, lower back, and hand/wrists. Logistic regression analysis revealed that there was a correlation between reports of WMSD in the neck and age (OR = 9.48) and health problems (OR = 6.71). Moreover, strong associations were found between MSDs in the shoulders, gender (OR = 5.88) and breaks between appointments (OR = 4.17). Conclusion: We concluded that the health problems diagnosed, work-related activities and gender contributed to musculoskeletal disorders in dentists in this clinic.
Keywords: Dentistry; Ergonomics; Musculoskeletal disorders; Occupational health